Identification Of Misconceptions Of Eighth Grade Students On Light Materials And Optical Devices - amanah firansilady; Sardianto Markos Siahaan; Syuhendri Syuhendri (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2022)
This study is a descriptive study that aims to analyze the understanding of the concept of students in science subjects on the material of light and optical devices as well as the causes of student misconceptions. This study was conducted on VIII grade students in SMP Negeri 5 Palembang. The subjects of this study were 100 eighth grade students in SMP Negeri 5 Palembang. The instrument used is a set of diagnostic tests consisting of 10 items of questions from physpot which has been translated and tested for validity. Data retrieval method is done by providing a test of understanding the concept of multiple choice questions as many as 10 items equipped with CRI (Certainty if Response Index) with a scale (0-5). In this study it was found that the average score obtained by students from the test is quite low at 50%. In addition, 9.28% had misconceptions, 38.5% did not understand the concept, and 28.5% had understood the concept. Some of the findings identified misconceptions include: (1) only white objects that can reflect light in a dark room, (2) points near the eyes of patients with hypermetropy, (3). light propagates about transparent objects and (4). light reflected from smooth surfaces.